Impact of formal teaching on medical documentation by interns in an emergency department in a Queensland teaching hospital. (13th January 2015) - Isoardi, Jonathon; Spencer, Lyndall; Sinnott, Michael; Eley, Robert
Abstract Objectives This study's objective was to determine whether tuition in medical documentation enhanced the ability of emergency medicine interns to produce effective medical records. Methods The study adopted a case control design, using a retrospective document audit methodology, following an education intervention during the 'More Learning for Interns in Emergency' (MoLIE) programme. It was conducted in a tertiary hospital that supports five 10 week rotations of 12 interns each year (n = 60). Controls were drawn from records written in March 2012 and cases from March 2013. A total of 250 medical records written by interns were audited, 125 from each year. Results Three categories of documentation were investigated: patient characteristics, clinical impressions and management plan using a purpose‐designed score sheet. Three individual items (differential diagnosis [DDX], Support and Impressions [Impress]) showed significant improvement. The proportion of excellent scores for DDX increased by 50% from 40.8% to 61.6%. A χ2 test for independence (with Yates continuity correction) indicated a significant association between the intervention and subsequent score (X2[1, n = 250] = 10.006, P < 0.001, phi −0.208). For Impress, a 48% increase in excellent scores was seen (39.2% to 58.4%). A χ2 test for independence indicated a significant association between the intervention and subsequent score (X2[2, n = 250] = 11.249, P = 0.004, Cramer's V 0.212). The variable Support also improved (X2[2, n = 250] = 8.297, P = 0.012, Cramer's V 0.189) with the number of excellent scores increasing from 37.6% to 48.0%. Conclusion The study demonstrated that documentation of clinical notes by interns can be enhanced by formal tuition.